A Philosophical Analysis of AI and Racism - Jones, Lel (Stance: an international undergraduate philosophy journal, 2020)
This paper addresses the problem of racism against Latinx and Black people in Artificial Intelligence (AI) and offers possible solutions. This ethical analysis is necessary because with a dramatic increase in the production of AI, the way we use it is critical in eliminating its current perpetuation of racism. I offer evidence of the current perpetuation of racism through AI by analyzing its use in banking and in law enforcement. I argue that the current way we produce and use AI needs to be seriously reconsidered and reinforce this argument with the use of Rawls’ theories of justice.